Maternal infection by Leishmania braziliensis in hamster does not influence the course of disease in progeny - Lima, Lia Fernandes; Frutuoso, Mercia Sindeaux; Oliveira, Augusto César Aragão; Figueiredo, Webertty M. Eufrásio; Pompeu, Margarida M. Lima; Teixeira, Maria Jania (Journal of Health & Biological Sciences, 2017)
Introduction: Immunoglobulins, soluble antigens, cells, cytokines and other immune system products can be transferred from infected mother to her offspring, leading to suppression or stimulation of immune response. Objective: To evaluate the influence of gender and maternal infection with Leishmania braziliensis in the course of the disease in the offspring of hamsters. Meodths: Offspring born from infected mother (IMO) or non-infected mother (NIMO) by Leishmania braziliensis, both sexes, was infected with the same strain of the mother after 30 days of life and followed for 18 weeks. We evaluated the thickness of the lesion, parasite load and histology of the lesions. Results: The number of parasite in both lesions and lymph node of IMO offspring showed a significant reduction in the 5th week post-infection compared to the NIMO offspring; however, this did not correspond to clinical symptoms. Histopathological analysis revealed that in the IMO offspring, the inflammatory process was more prominent. In relation to gender, it was observed that the male offspring showed lesion thickness and higher parasite burden than females. Conclusion: Maternal infection by L. braziliensis in hamsters does not appear to influence the course of the disease in the homologous offspring infection, as well as the male offspring presented augmented susceptibility to L. braziliensis infection regardless of whether they were born from IMO or NIMO. Also, the reduction of the granuloma index in the IMO offspring, together with the higher inflammatory response, suggests a less effective cellular response in the chronic phase of the disease in these animals.